1966
DOI: 10.1038/bjc.1966.90
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cell population kinetics of transplanted tumours of widely-differing growth rate.

Abstract: THE principal object of studies of the cell population kinetics of tumours is to explain how a tumour attains its particular growth rate, and thus to make a more informed judgement on methods of growth control. The growth rates of tumours show wide variations, both between and within individual species. In man, volume doubling times for primary and secondary lung tumours range from about two weeks to many months (Steel and Lamerton, 1966); in experimental animals, spontaneous tumours with volume doubling times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

1968
1968
1977
1977

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…The difference between the distributions of doubling time for tumours in domestic animals and man may be significant (P = 0'05, calculated from the distributions of the logarithm of doubling time). A comparison of labelling indices is also consistent with a slightly higher growth rate in the animal tumours: the median labelling index for the tumours in the present series is about 5 %, as compared with a median of 3 % for a group of 170 human tumours (Steel, 1967). While these differences are in the direction which one might expect from the differences in lifespan they are nevertheless sufficiently small to confirm the basic starting point of this work that spontaneous tumours in domestic animals serve as a good model for human cancer.…”
Section: Studies Of Thymidine Labellingsupporting
confidence: 88%
See 2 more Smart Citations
“…The difference between the distributions of doubling time for tumours in domestic animals and man may be significant (P = 0'05, calculated from the distributions of the logarithm of doubling time). A comparison of labelling indices is also consistent with a slightly higher growth rate in the animal tumours: the median labelling index for the tumours in the present series is about 5 %, as compared with a median of 3 % for a group of 170 human tumours (Steel, 1967). While these differences are in the direction which one might expect from the differences in lifespan they are nevertheless sufficiently small to confirm the basic starting point of this work that spontaneous tumours in domestic animals serve as a good model for human cancer.…”
Section: Studies Of Thymidine Labellingsupporting
confidence: 88%
“…Among the dog tumours of this series there were other examples of what was apparently a wide distribution of grain counts; as was noted in the discussion of case 5 it was difficult to find an autoradiographic exposure which allowed recognition of the low-labelled cells without heavy labelling obscuring the appearance of other nuclei. When applied to tumour cell populations in which cell loss occurs, T has been called the potential doubling time (Steel, 1967). A theoretical discussion of the parameter A has been presented (Steel, 1968) where it is shown that although A has a possible range of values from 0 7 to 1-4, values higher than unity are unlikely, and when the population doubling time is longer than 2 days, A will be within the range 0 7 to 0 8.…”
Section: Studies Of Thymidine Labellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented here are from studies designed to relate quantitatively the effects of 5-FU at a cellular level with the observed retardation of tumour growth. Methods available for growth fraction (Mendelsohn, 1962;Steel, Adams and Barrett, 1966) and cell loss (Steel, 1968) determinations by 3H-thymidine incorporation do not account for wide fluctuations resulting from residual synchrony from the pulse label and from the transition of growing to non-growing cells. Perturbations in cellular proliferation and cell killing resulting from cycle-specific drugs such as 5-FU would only magnify the fluctuations in both these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the size of s.c. and i.m. tumours were made by the calibration curve technique (Steel, Adams and Barrett, 1966). For s.c. tumours the product of two superficial diameters was used as a measure of tumour size, and for i.m.…”
mentioning
confidence: 99%